2019
DOI: 10.1016/j.jenvman.2019.109526
|View full text |Cite
|
Sign up to set email alerts
|

Removal and monitoring acetaminophen-contaminated hospital wastewater by vertical flow constructed wetland and peroxidase enzymes

Abstract: Hospital wastewater contains acetaminophen (ACT) and nutrient, which need adequate removal and monitoring to prevent impact to environment and community. This study developed a pilot scale vertical flow constructed wetland (CW) to (1) remove high-dose ACT and pollutants in hospital wastewater and (2) identify the correlation of peroxidase enzyme extruded by Scirpus validus and pollutants removal efficiency. By that correlation, a lowcost method to monitor pollutants removal was drawn. Plants, such as Scirpus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 57 publications
0
23
0
2
Order By: Relevance
“… 1.2 m 3 /day Pilot-scale [87] Study 31 Switzerland Ozonation- 1.08 gO 3 /g Dissolved organic carbon 12 to 23 L/h Pilot-scale [88] Study 32 Switzerland PAC- 23 mg/L 180 L/day Pilot-scale [88] Study 33 Switzerland UV- 2400 J/m 2 600 L/h Pilot-Scale [88] Study 34 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by Ozonation- 1.08 gO 3 /g Pilot-scale [88] Study 35 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by PAC- 23 mg/L Pilot-scale [88] Study 36 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by UV- 2400 J/m 2 Pilot-scale [88] Study 37 Thailand Vertical flow CW (1.5 m length, 0.6 m width and 0.6 m depth), The media bed contained sand, pea gravel and gravel with respective height of 0.1, 0.2, and 0.4 m from top to bottom. 75 to 85 L/day 5 days Pilot-scale [99] Study 38 <...>…”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 1.2 m 3 /day Pilot-scale [87] Study 31 Switzerland Ozonation- 1.08 gO 3 /g Dissolved organic carbon 12 to 23 L/h Pilot-scale [88] Study 32 Switzerland PAC- 23 mg/L 180 L/day Pilot-scale [88] Study 33 Switzerland UV- 2400 J/m 2 600 L/h Pilot-Scale [88] Study 34 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by Ozonation- 1.08 gO 3 /g Pilot-scale [88] Study 35 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by PAC- 23 mg/L Pilot-scale [88] Study 36 Switzerland MBR ( Chamber 1 is oxic and chamber 2 is anoxic) followed by UV- 2400 J/m 2 Pilot-scale [88] Study 37 Thailand Vertical flow CW (1.5 m length, 0.6 m width and 0.6 m depth), The media bed contained sand, pea gravel and gravel with respective height of 0.1, 0.2, and 0.4 m from top to bottom. 75 to 85 L/day 5 days Pilot-scale [99] Study 38 <...>…”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%
“…Vo et al (2019) observed more than 99% removal of paracetamol and more than 80% removal for TSS, COD, and ammonia. However, only 22% of TN was removed, indicating incomplete denitrification of nitrate and nitrite [99] .…”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%
“…Some investigations aimed to better understand the removal mechanisms of key compounds and their interactions with the treatment environment. This is the case of the investigations by ( 21 ) who tried to correlate the concentrations of acetaminophen and peroxidase enzymes in a pilot vertical subsurface flow system fed with hospital effluent in order to evaluate if the selected enzymes could be assumed as indicators of the occurrence of acetaminophen, thus reducing its monitoring costs.…”
Section: Scope Of the Selected Recently Published Investigationsmentioning
confidence: 99%
“…Over the last two to three years, interesting investigations on the treatment of hospital effluent have been carried out worldwide: consolidated and modified/enhanced technologies as well as new solutions have been tested on the effluent of specific wards, the whole healthcare structure, nursing homes specialised in psychiatric diseases ( 22 ), ( 23 ) or service units such as laundry ( 24 ). They have not only taken place in countries where studies or investigations on hospital effluent have also been carried out, but also in new ones, such as Ethiopia ( 25 ), Columbia ( 5 ), India ( 26 ), Iran ( 27 ), ( 28 ), Costa Rica ( 29 ) and Thailand ( 21 ). This demonstrates the increasing interest in the management and treatment of healthcare structure effluent by researchers, practitioners, policy makers and administrative staff, both in developed and developing countries.…”
Section: Perspectives In the Treatment Of Hospital Effluentmentioning
confidence: 99%
“…Most of these substances are endocrine disruptors and toxic to humans and the environment [5,6]. Reducing the input of micropollutants into the environment has become a major issue for the preservation of resources and public health [7].…”
Section: Introductionmentioning
confidence: 99%